EFEKTIVITAS MENGKONSUMSI JUS STROBERI DALAM MENGHAMBAT PERTUMBUHAN BAKTERI RONGGA MULUT - Dyah Setyorini; Niken Probosari (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2012)
Flow of saliva constitutes certain natural process which can be able cleansing food residue from teeth surface and for the same time to protect mouth tissue from bacteria influence. One of fruits contains much nutrition is strawberry. Strawberry fruit is contain of xylitol have characteristic to obstruct growth of bacteria in oral cavity. The aim of this study is to know the influence consumption strawberry juice toward amount growth colony of saliva bacteria in the oral cavity. Subjects of research have 16 people from the population which take with purposive sampling method. Result of data research on test with Kolmogorov-Smirnov and Levene test to find out which data distribution normal and homogeneous, Furthermore with parametric test analysis variants one way with level of trust 95%(α=0,005). Furthermore with Tukey-HSD test. Result from this research with consumption beverage of strawberry juice can reduce amount colony of saliva bacteria and can obstruct growth colony bacteria in the oral cavity.